Alternative migratory locust phenotypes are associated with differences in the expression of genes encoding the methylation machinery. Issue 2 (27th November 2015) - Robinson, K. L.; Tohidi‐Esfahani, D.; Ponton, F.; Simpson, S. J.; Sword, G. A.; Lo, N.
Abstract: Despite the importance of locust density‐dependent polyphenism as a model system for understanding phenotypic plasticity, there is still much to be learnt about its underlying molecular control. Here we describe the first investigation into the expression of genes encoding the DNA methylation machinery in the migratory locust ( Locusta migratoria ). We show that the alternative solitarious and gregarious phenotypic states induced by different locust rearing densities are associated with significant differences in the expression of the target genes DNA methyltransferase 1, DNA methyltransferase 2 and methyl‐CpG‐binding domain protein 2/3 . This variation was most pronounced in the embryos of solitarious vs. gregarious mothers. We mapped the embryonic methylation profiles of several intragenic regions and a Long Interspersed Nuclear Element (LINE), each of which is known to be differentially expressed between alternative locust phenotypes or has been directly implicated in phase change. LmI and three genes, adenyl cyclase‐associated binding protein 2, choline kinase alpha‐ like and henna, were methylated. Our results set the stage for future studies investigating the specific role of DNA methylation in the maternal transfer of migratory locust phase polyphenism.